Planificación territorial: Elección multicriterio interactiva del patrón de urbanización : estudio de caso: Río Cuarto, Córdoba, Argentina; Territorial planning: Interactive multi-criteria decision for urban patterns : case study: Río Cuarto, Córdoba, Argentina - Jorge Dante De Prada; Américo Degioanni; José Manuel Cisneros; Alberto Cantero Gutiérrez; Horacio Alfredo Gil; Diego Sebastián Tello; Cecilia Inés Pereyra; Óscar Giayetto (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2018)
– The goal of this paper is to analyze the local government's perception about the significance of a discrete multi-criteria method for assessing proposals for urban expansion (PUE). The study case was performed, by using PROMETHEE method, in Río Cuarto, Córdoba, Argentina. The decision matrix consists of five PUEs: one corresponding to a sparse settlement, trend PUE1, and four for compact settlements, PUE2, PUE3, PUE4 and PUE5, where seven criteria are considered: "Loss of Agricultural Income" (LAI), "Population", "Loss of Ecosystem Services" (LES), "Investment Costs in Road Infrastructure" (Road-IC), "Urban Solid Waste Collection" (USWC), "Range of Public Service Networks" and "Political-Institutional Effort" (PIE). Local government's preferences were disclosed by means of a workshop where: the decision matrix was analyzed; and the relative significance that government members assign to each criterium was asked. Results show that PUE4 and PUE2 were considered in the most selected proposals. In comparison with PUE1, PUE4 saves 162 millions (due to a lower LAI and Road-IC); it requires 35% less in Range of Networks and 11% less in USWC, although this is the PUE that requires a significantly greater PIE. When considering PUE2, this option saves 196 millions and requires 51% less in Range of Networks and 37% in USWC. However, PUE2 imposes the greatest PIE in relation with PUE1 and houses less inhabitants than PUE4. Government members attach much importance to an approach based on the multi-criteria method to decide a vision of the territory for the future.
Keywords: C61; O21; R14; 330; Territorial planning; settlement; multi-criteria decision; demo- graphic policy; sustainable development